Islamisasi Ilmu Melalui Pendidikan Dayah di Aceh: Telaah terhadap Peran Tengku dan Kurikulum Tradisional - Muhammad Mulyakhan (Raudhatun Najah Publisher, 2024)
This study aims to analyze how the Islamization of knowledge is implemented through dayah education in Aceh by highlighting two main aspects: the role of the tengku as an agent of Islamization and the traditional dayah curriculum as an instrument for strengthening Islamic values in the learning process. The method used is library research with a qualitative approach and descriptive-analytical analysis, employing primary sources from the works of Islamic thinkers such as Syed Muhammad Naquib al-Attas and Ismail Raji al-Faruqi, as well as local literature on Acehnese dayah education. The results show that the role of the tengku in transmitting Islamic values through exemplary conduct and tauhid-based teaching is crucial in shaping the students’ epistemology. Meanwhile, the traditional dayah curriculum has proven to be an effective instrument in preserving the authenticity of Islamic scholarship. Nevertheless, to address the challenges of the modern era, it is necessary to strengthen both the curriculum and teachers’ capacities so that dayah institutions can remain relevant, adaptive, and sustainable centers for the Islamization of knowledge.